2022
DOI: 10.1155/2022/6917593
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Monetary Policy and Housing Price Change Based on a VAR Model

Abstract: In early 2020, the global economy was severely hit by the COVID-19 pandemic. Governments, including China, have adopted expansionary fiscal policies to stimulate demand and quantitative easing to increase the money supply to boost the economy by lowering lending rates. This paper starts from the influence of monetary policy on housing price mechanism, tries to explore the monetary policy on interest rate and money supply, finally establishes the VAR model, empirically analyzes the effectiveness of the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…More specifically, a 1 percent increase in money supply leads to a 3.212 percent increase in the housing affordability index in the long run and a 1.154 percent increase in the short run. This aligns with the results obtained by Feng (2022), who identified a stable and positive long-term correlation between real estate prices and the broad money supply. Furthermore, Yin et al (2020) elucidated that the expansion of the money supply led to an excess of funds, thereby increasing the demand for residential properties, and ultimately driving an upsurge in prices, exacerbating housing affordability issues in Malaysia.…”
Section: Co-integration Test Resultsupporting
confidence: 92%
See 2 more Smart Citations
“…More specifically, a 1 percent increase in money supply leads to a 3.212 percent increase in the housing affordability index in the long run and a 1.154 percent increase in the short run. This aligns with the results obtained by Feng (2022), who identified a stable and positive long-term correlation between real estate prices and the broad money supply. Furthermore, Yin et al (2020) elucidated that the expansion of the money supply led to an excess of funds, thereby increasing the demand for residential properties, and ultimately driving an upsurge in prices, exacerbating housing affordability issues in Malaysia.…”
Section: Co-integration Test Resultsupporting
confidence: 92%
“…However, the result of their study postulates that the response of housing price to the shock of money supply are notably more pronounced in the urban centers of Brisbane, Canberra, and Perth, relative to other major capital cities across Australia. These findings are in line with two other studies conducted by Yin et al (2020) and Feng (2022) in mainland China. In the case of Yin et al (2020), their study similarly identified a co-movement between housing prices and money supply, particularly in the short term, with this relationship becoming even more pronounced in the medium term.…”
Section: Monetary Sector Variables and Housing Affordabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore the central bank and government officials may ensure stability in the housing market by making the necessary legal regulations regarding money supply and interest rates. (Feng 2022). Besides that, in the case about Turkey's house price dynamics, the house bubble risk is analysed through cointegration test and the findings state that construction cost and rent are positively but mortgage interest rate is negatively related to house price.…”
Section: Resultsmentioning
confidence: 99%
“…In the long term, the effect of money supply policies rather than interest rate may be greater on house prices. In this way central bank can easily adapt money supply policies to be able to regulate housing market (Feng, 2022).…”
Section: Introductionmentioning
confidence: 99%